Is it possible to modify the obesogenic environment? - Brazil case - Fisberg, Mauro (2019)
In recent decades, the prevalence of obesity has reached increasingly high rates among children and adolescents worldwide as the result of interactions between obesogenic environments and genetics. In Brazil, a middle-income country, the rates of overweight and obesity reached 18.9% and 8.7%, respectively, in 2015, corresponding to a prevalence of excess weight of 27.6%. Concomitant with these worrying data, the prevalence of insufficient physical activity in adolescents is 66.2% based on objective accelerometer measurements. The Brazilian government has taken concrete actions to contain the advance of obesity and physical inactivity and is taking part in political efforts combined with scientific evidence to develop laws, programs, and guidelines. While access to food outside the home, with the unstoppable intake of sweet beverages, sodium, and fat, is contributing to increased obesity, a lack of physical activity in leisure time or transportation must also be considered. However, while Brazil has been taking actions to address the obesogenic environment, with a view to reduce the prevalence and incidence of obesity and physical inactivity, more efforts are needed to implement these actions and approve measures that are still in progress.